Design and Synthesis of New Pharmaceutical Compounds as Potent Α-Glucosidase Inhibitors and their Role in the Treatment of Type II Diabetes Mellitus - Abd, Ola Hussein Noor; Kazim, Noor Kazim Hashim; Hussein, Laith Aziz Jebur; Hamza, Mosadeq Ameer Hasson (American Journal of Biomedicine and Pharmacy, 2025)
Despite many effective treatments, Type II Diabetes (T2D) remains a critical health issue, affecting hundreds of millions globally. The well-established T2D treatment strategy of inhibiting α-glucosidase—the critical enzyme in carbohydrate metabolism—offers new opportunities to advance therapeutic options. A rational design strategy targeting α-glucosidase has been established, and new inhibitors with improved potency, selectivity, and bioavailability have been designed and synthesized . With anticipated oral bioavailability and sustained postprandial control, these compounds exhibit strong translational potential for supporting T2D management. Approximately 542 million adults are currently living with diabetes, with elevated blood glucose levels being the central common denominator for this epidemic. These distressing figures are continuing to rise at alarming rates across the globe, with Type 2 Diabetes (T2D) accounting for a staggering 90% of all the cases. The burden that this condition places on human health, as well as on healthcare systems worldwide, is truly staggering, and growing more severe with time. Despite this, the discovered approaches for its effective management—including the inhibition of α-glucosidase—remain indispensable and critically important. The extensive exploration of α-glucosidase inhibitors has yielded only modest progress in drug development, which highlights the ongoing need for novel therapeutic candidates in this area. Indeed, multiple agents aimed at targeting α-glucosidase are extensively used around the world, and thus they constitute a subject of notable research attention and focus among healthcare professionals and researchers alike.